Microphysiologic Human Tissue Constructs Reproduce Autologous Age-Specific BCG and HBV Primary Immunization in vitro - Sanchez-Schmitz, Guzman; Stevens, Chad R.; Bettencourt, Ian A.; Flynn, Peter J.; Schmitz-Abe, Klaus; Metser, Gil; Hamm, David; Jensen, Kristoffer J.; Benn, Christine; Levy, Ofer (Frontiers in Immunology, 2018)
Current vaccine development disregards human immune ontogeny, relying on animal models to select vaccine candidates targeting human infants, who are at greatest risk of infection worldwide and receive the largest number of vaccines. To help accelerate and de-risk development of early-life effective immunization, we engineered a human age-specific microphysiologic vascular-interstitia interphase, suitable for pre-clinical modeling of distinctive age-targeted immunity in vitro. Our Tissue Constructs (TCs) allow for autonomous extravasation of monocytes that undergo fast self-directed differentiation into migratory Dendritic Cells (DCs) in response to adjuvants and vaccines such as Bacille Calmette-Guérin (BCG) or Hepatitis B virus Vaccine (HBV). TCs contain a confluent human endothelium grown atop a tri-dimensional human extracellular matrix substrate, employ human age-specific monocytes and autologous non heat-treated plasma, and avoid the use of xenogenic materials and exogenous cytokines. Self-developed DCs from vaccine-pulsed TCs were able to induce single-antigen recall proliferation and cytokine responses from autologous naïve and memory CD4+ T lymphocytes, matching current vaccine immune-status of study participants. Overall, our microphysiologic culture method reproduced same age- and antigen-specific recall responses to BCG and HBV immunization, as those observed after a birth immunization of human cohorts in vivo, offering for the first time a new approach to early pre-clinical selection of effective age-targeted vaccine candidates.